Revisiting the Relationship between Micro and Macro Social Work Practice. Issue 4 (October 2016) - Austin, Michael J.; Anthony, Elizabeth K.; Knee, Ryan Tolleson; Mathias, John
This analysis seeks to bridge the differences between micro and macro practice within the context of the shared mission of social work. The search for common ground, given decades of specialization, includes the identification of the different ways that the two forms of practice can inform each other, describes core workplace skills relevant to interventions at the micro and macro levels of organizational and community life, and explores the need for bilingual capacities to enhance communications between both domains of social work practice. It concludes with implications for future curricular changes.